Pemanfaatan Augmented Reality Sebagai Media Pengenalan Buah-buahan Berbasis Android - Akbar, Kevin Azrial; Listyorini, Tri; Supriyati, Endang (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2022)
Technological developments have increased very rapidly in various aspects, one of which is Augmented Reality (AR) technology in the field of education. By introducing the types of fruits that display 3D images and also the benefits of fruits, it can provide education to the public. This application was made using the Multimedia Development Life Cycle (MDLC) method.. The results of testing this android-based application are expected to facilitate the provision of information on the benefits of fruits using Augmented Reality (AR) technology